Validity of the timed 25-foot walk as an ambulatory performance outcome measure for multiple sclerosis - Motl, Robert W; Cohen, Jeffrey A; Benedict, Ralph; Phillips, Glenn; LaRocca, Nicholas; Hudson, Lynn D; Rudick, Richard (Multiple sclerosis, 2017)
The Multiple Sclerosis Outcome Assessments Consortium (MSOAC) includes representatives from advocacy organizations, Food and Drug Administration (FDA), European Medicines Agency (EMA), National Institute of Neurological Disorders and Stroke (NINDS), academic institutions, and industry partners along with persons living with multiple sclerosis (MS). One of the MSOAC goals is acceptance and qualification by regulators of performance outcomes that are highly reliable and valid, practical, cost-effective, and meaningful in MS. This article addresses the history, application, and psychometric properties of one such MSOAC metric of ambulation or walking namely, the timed 25-foot walk (T25FW). The T25FW has strong reliability over both brief and long periods of time in MS across a large range of disability levels. The outcome of walking speed from the T25FW has obvious real-world relevance and has correlated strongly with other measures of walking and lower extremity function. The T25FW is responsive for capturing intervention effects in pharmacological and rehabilitation trials and has an established value for capturing clinically meaningful change in ambulation. Directions for future research involve validating clinically meaningful improvements on the T25FW as well as determining whether 20% change is clinically meaningful across the disability spectrum. Researchers might further consider synchronizing accelerometers and motion sensors with the T25FW for capturing walking speed in everyday life and the patient's real environment.